In vitro assessment of the indirect antioxidant activity of Sulforaphane in redox imbalance vanadium-induced. Issue 22 (17th November 2017) - Visalli, Giuseppa; Facciolà, Alessio; Bertuccio, Maria Paola; Picerno, Isa; Di Pietro, Angela
Abstract: Owing to sulforaphane presence, a dietary consumption of Brassicac e ae prevents chronic diseases. This hormetic compound induces adaptive stress response at subtoxic doses, while doses that exceed the cellular defence are toxic. In HepG2, Caco-2 and Vero cells, we investigated the sulforaphane (SFN) (5 μM) role in counteracting redox imbalance induced by VOSO4 [V(IV)]. 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) test showed a dose-dependent viability reduction ( r < −0.95; p < 0.01) (range 5–80 μM). At 5 μM, SFN enhancement of mitochondrial activity was confirmed by Δ ψ m ( p < 0.05) both in basal condition and in redox-stressed cells. Intracellular ROS, DNA and lysosomal oxidative damages underlined the indirect antioxidant SFN activity, confirmed by the increase of GSH. The SFN empowering effects on mitochondrial function were imputable to the presence of mitochondrial proteins among the Nrf2-responsive phase II proteins. Considering the link between oxidative stress and chronic diseases, a long-term dietary intake of Brassicac e ae could be strongly advisable. Abstract :